AGE DETERMINATION OF MARINE SEDIMENT IN SPERMONDE ARCHIPEL VIA ACTIVITY MEASUREMENT OF 14C BY LSC (LIQUID SCINTILLATION COUNTING) - Sheila Aprilia; Muhammad Zakir (Marina Chimica Acta, 2014)
A research on Age Determination of Sea Sediment of Spermonde Islands through Ac- tivity Measurements of 14C with LSC (Liquid Scintillation Counting) method has been performed. The sample of sediment was taken at the island of Lae-Lae, Spermonde Islands where it is rela- tively close to the influence of human activities. This study aims to determine the activity of 14C in the sediment sample and calculate the age through measurement of 14C specific activities of  sedi- ment sample.  Preparation is done both physically and chemically by using a mixture of solution of the acid and alkaline: NaOH, H2O2, HClO4, and HCl to produce sediment sample which was white and clean with a weight reduction of up to 5 %.  Carbonate matrix sample was separated as CO2 using 1 N KOH absorber with H3PO4  85 %. Carbon content of the sample solution is 1.172 g/8 mL.  The 14C activity of the sample was analyzed using LSC (Liquid Scintillation Counting) as an analysis technique. The specific activity sediment sample was 13.85g/C. The age of sediment sam- ple calculated from the specific activity was 821,0822 year.